Pengelolaan Hipertermia dengan Water Tepid Sponge pada Anak Prasekolah Dengan Demam Thypoid - Wening Tiyasasrini; Siti Haryani (Universitas Ngudi Waluyo, 2026)
Typhoid fever falls into the category of septic fever, where the body temperature increases gradually, reaching a high peak at night, and then returning to above normal levels in the morning. In addition, sufferers often experience complaints such as shivering and sweating. When the high fever returns to normal, this condition is also known as hectic fever.Therefore, increasing awareness of sanitation and clean living behavior is very important to prevent the spread of this disease. This writing aims to identify the problems experienced, provide a problem-solving plan and take action to solve the problem, evaluate the problem. The writing method used is a descriptive method that aims to describe the management of nursing care for typhoid fever that experiences an increase in body temperature above the normal range as the main problem. The approach used includes a series of steps in nursing care, starting from assessment, data analysis, formulating nursing diagnoses, nursing actions or nursing planning, to implementation and evaluation of nursing. The report on the management of water tepid sponges was carried out for 3 days in typhoid fever patients with data collection techniques using interviews, physical examinations, observations, and case management. The results showed that providing water tepid sponge actions was able to lower body temperature, improve skin temperature. Based on the nursing actions taken, it can be concluded that the patient’s body temperature is under control. Advice for the patient’s family: an active role in the family is very necessary in supporting the psychology and motivation of the child. ABSTRAK Demam thypoid termasuk dalam kategori demam septik, di mana suhu tubuh meningkat secara bertahap, mencapai puncaknya yang tinggi di malam hari, dan kemudian kembali turun ke tingkat di atas normal pada pagi hari. Selain itu, penderita sering mengalami keluhan seperti menggigil dan berkeringat. Ketika demam tinggi tersebut kembali normal, kondisi ini juga dikenal sebagai demam hektik. Penulisan ini bertujuan mengidentifikasi masalah yang dialami, memberikan rencana penyelesaian masalah dan melakukan tindakan penyelesaian masalah, mengevaluasi masalah. Metode penulisan yang digunakan metode deskriptif yang bertujuan untuk menggambarkan pengelolaan dengan asuhan keperawatan demam thypoid yang mengalami kenaikan suhu tubuh diatas rentang normal sebagai masalah utama. Adapun Teknik pengambilan sample yang digunakan adalah purposive sampel, dimana peneliti memilih subjek atau unit analisis berdasarkan tujuan penelitian dan kriteria tertentu yang relavan. Pendekatan yang digunakan mencakup serangkaian langkah dalam asuhan keperawatan, mulai dari pengkajian, analisa data, merumuskan diagnosis keperawatan,perencanaan keperawatan, hingga implementasi dan evaluasi keperawatan. Laporan pengelolaanwater tepied sponge dilakukan selama 3 hari pada pasien demam thypoid dengan teknik mengumpulkan data menggunakan wawancara, pemeriksaan fisik, observasi, dan pengelolaan kasus. Hasil menunukkan bahwa water tepid sponge mampu menurunkan suhu tubuh membsik, suhu kulit membaik. Berdasarkan tindakan keperawatan yang dilakukan, maka dapat disimpulkan termoregulasi pasien teratasi. Saran bagi keluarga pasien peran aktif dalam keluarga sangat diperlukan dalam mendukung psikologis serta motivasi pada anak.